Measuring the Shared Fate of IGP Engineering and Interdomain Traffic - Agarwal, Sharad; Nucci, Antonio; Bhattacharyya, Supratik (ICNP, 2005)
Typically, each Autonomous System (AS) tunes its local IS-IS or OSPF metrics without any coordination with other ASes. Such local optimizations can lead to sub-optimal end-to-end network performance, as suggested by the performance enhancements achieved by some overlay routing projects. We study the interaction of local IGP engineering in an ISP network with interdomain routing policies. Specifically, (a) how does hot-potato routing (the BGP policy of choosing the closest egress) influence the selection of IGP link metrics? and (b) how does traffic to neighboring ASes shift due to changes in the local AS¿s IGP link metrics?In our measurement study, we find that the hot-potato routing policy interacts significantly with IGP engineering - ignoring this interaction resulted in metrics sub-optimal by as much as 20% of link utilization. Further, the impact on neighboring ASes depends on peering locations and policies, and as much as 25% of traffic to a neighboring AS can shift the exit point. Such interdomain shifts can be detrimental to the performance of neighboring ASes. We rely on the actual measured network topology, IGP metrics, traffic matrix and delay bounds. Even though our results are specific to a single ISP, they show significant interaction between local IGP engineering and interdomain routing policies, and thus motivate further work on global network optimization and coordination among ISPs.